Corporate Social Responsibility in Liquid Times: The Case of Romania - Grigore, Georgiana; Molesworth, Mike; Vontea, Andreea; Basnawi, Abdullah Hasan; Celep, Ogeday; Jesudoss, Sylvian Patrick (Journal of business ethics, 2021)
Existing scholarly work on corporate social responsibility (CSR) frequently emphasizes either normative/ethical claims about social progress or instrumental/strategic claims about corporate effectiveness, yet less often acknowledges the moral conditions of those undertaking CSR within a specific cultural context. In this paper, we draw attention to the social conditions in which CSR takes place and the related ethics of the subjects that must enact it. Our approach is to document the lived experiences of practitioners in Romania, a post-communist society. Drawing from fifty-three depth interviews with both corporate responsibility practitioners, and managers in non-profit organizations who together work on CSR projects, we describe their experiences of the social and organizational environment, the CSR practices that are undertaken in this context, and the intended and unintended consequences of such work. Using Bauman's theorization of ethics, including adiaphora and moral distancing, and Borfun's interpretation of Romanianness, we then theorize liquid CSR as an ambivalence between adiaphoric practice (instrumental morality, careerism and self-interest) and the moral impulse to do good, resulting in both intended (short-term promotion and competitive victimhood) and unintended consequences (a potential for corruption and collateral beneficiaries).